ДВУХРОТОРНАЯ МАГНИТОЭЛЕКТРИЧЕСКАЯ СИСТЕМА ВОЗВРАТНО-ВРАЩАТЕЛЬНОГО ДВИЖЕНИЯ И ЕЕ МАТАМАТИЧЕСКАЯ МОДЕЛЬ - Филоменко , А.А. (Інститут електродинаміки НАН України, Київ, 2014)
We propose a method for reducing vibration exposure to the operator's hand drive reciprocating rotary motion. We consider a system of two diametrically magnetized driven rotors that perform reciprocating rotary motion in different directions. The mathematical model of a system of two magnetized rotors based on the fundamental principle of integral Hamilton. References 4.